Medical Management of Male Infertility in the Absence of a Specific Etiology - Gudeloglu, Ahmet; Brahmbhatt, Jamin V.; Parekattil, Sijo J. (Seminars in Reproductive Medicine, 2014)
Idiopathic male infertility can be diagnosis in approximately one-third of infertile males. The empirical medical treatment with or without assisted reproductive techniques appears common in male infertility practice. This type of management can be classified as hormonal treatment including gonadotropins, antiestrogens, and aromatase inhibitors and support with antioxidant supplements such as carnitine, lycopene, glutathione, and vitamin E. This review investigates the evidence of commonly used empirical medical management of male infertility when there is no demonstrable diagnosis.
Keywords: idiopathic male infertility; empirical medical treatment; gonadotropins; antiestrogens; aromatase inhibitors; clomiphene; anastrozole; antioxidants; carnitine; lycopene